Religiosity of Muslim Customers as a Motivation to Save at Bank Syariah Indonesia - Makka, Misbahul Munir; Fahmi, Chairul; Tarantang, Jefry (Kunuz: Journal of Islamic Banking and Finance, 2024)
This research explores the perception and motivation of saving from customers of the Branch Office (KC) Bank Syariah Indonesia (BSI) in Manado. This study uses a qualitative approach to understand how customers view Islamic banking services and the factors motivating them to use them. The research method includes in-depth interviews with BSI customers. Interviews are used to explore customers' views on Islamic banking services, the factors influencing their savings decisions, and their experiences and expectations regarding these services. The findings show that religiosity, income, and understanding of Sharia principles are essential in the motivation to save in Islamic banks. Customers choose Islamic banks not only because of their religious aspects but also because they believe in transparency and fairness in financial services based on Islamic teachings. The implications of this research are important for Islamic banks in designing more effective marketing strategies and products that suit the needs of customers with a solid religious background.